Acute renal failure, COVID-19 and deaths, worrying rates in intensive care units: a cross-sectional study - Watanabe, Yoshimi José Ávila; Carvalho, Lívia Maria Rezende; Guedes, João Victor Marques; Baldoni, André Oliveira; Belo, Vinícius Silva; Otoni, Alba (São Paulo Medical Journal, 2025)
BACKGROUND: Acute kidney failure is a serious consequence of coronavirus disease 2019 (COVID-19). OBJECTIVES: To identify the prevalence of COVID-19, kidney failure, frequency of death, and associated factors in patients receiving intensive care. DESIGN AND SETTING: Analytical cross-sectional study conducted in the intensive care unit (ICU) of a medium-sized philanthropic general hospital in center-west Minas Gerais. METHODS: Adults and older individuals who underwent real-time polymerase chain reaction testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were evaluated by the nephrology team. RESULTS: Among the 176 patients, the prevalence of COVID-19 and acute kidney injury (AKI) were 103 (58.5%) and 132 (75%), respectively, and 44 (25%) had chronic kidney disease (CKD) and 16 (15,5%) were positive for SARS-CoV-2. In the Charlson index classification, which estimates the risk of death, a statistically significant difference was identified in the percentages of groups with and without COVID-19 for indices 0, 1, and 2. There was a significant association between kidney disease and ICU mortality (P < 0.05). Patients with CKD had fewer fatal outcomes (13/97, 13.4%) than those with AKI (85/97, 87.6%). CONCLUSIONS: COVID-19 rates remained high long after diagnosis and prevention of SARS-CoV-2 infection. In addition, a higher death rate among patients who developed AKI, whose prevalence was also greater than that in the national literature, regardless of the presence of COVID-19, revealed a worrying scenario and corroborated the need for early and judicious approaches to preserve the lives of patients with AKI admitted to intensive care units.